Pig models for Duchenne muscular dystrophy – from disease mechanisms to validation of new diagnostic and therapeutic concepts - Stirm, Michael; Fonteyne, Lina Marie; Shashikadze, Bachuki; Stöckl, Jan B.; Kurome, Mayuko; Keßler, Barbara; Zakhartchenko, Valeri; Kemter, Elisabeth; Blum, Helmut; Arnold, Georg J.; Matiasek, Kaspar; Wanke, Rüdiger; et al. (Neuromuscular Disorders, 2022)
Duchenne muscular dystrophy (DMD) is a fatal X-linked disease caused by mutations in the DMD gene, leading to complete absence of dystrophin and progressive degeneration of skeletal muscles and heart. Animal models are essential for preclinical evaluation of novel diagnostic procedures and treatment strategies. Gene targeting/editing offers the possibility of developing tailored pig models for monogenic diseases. The first porcine DMD model was generated by deletion of DMD exon 52 (DMDΔ52) in cultured kidney cells, which were used for somatic cell nuclear transfer to produce DMDΔ52 offspring. The animals resembled clinical, biochemical, and pathological hallmarks of DMD, but died before sexual maturity, thus preventing their propagation by breeding. This limitation was overcome by the generation of female heterozygous DMDΔ52 carrier pigs, which allowed the establishment of a large breeding colony. In this overview, we summarize how porcine DMD models have been used for dissecting disease mechanisms, for validating multispectral optoacoustic tomography as an imaging modality for monitoring fibrosis, and for preclinical testing of a CRISPR/Cas9 based approach to restore an intact DMD reading frame. Particular advantages of porcine DMD models include their targeted design and the rapid disease progression with early cardiac involvement, facilitating translational studies in reasonable time frames.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Duchenne muscular dystrophy; Gene editing; Optoacoustic imaging; Pig model